Comparison of compression therapy use, lower limb wound prevalence and nursing activity in England: a multisite audit. (2nd December 2022) - Hopkins, Alison; Samuriwo, Ray
Abstract : Objective: This audit was designed to identify the need of the population and the clinical activity associated with wounds and the management of lower limb swelling. The exploration focused on lower leg wound management, access to diagnostics and compression therapy across each audit site. The variation across the sites was explored to gather insight into the real-world barriers to providing evidence-based management for leg ulceration. Method: We undertook wound prevalence audits across six diverse community provider sites in England. The audit was undertaken by the local providers, with the inclusion of tissue viability and podiatry leads and key local stakeholders, often local quality leads, primary care leads and nursing directors. Each audit was undertaken with full engagement of local clinicians. Data were collected centrally, and each audit site received their own local analysis and report, with additional analytical support from the local tissue viability lead to ensure the feedback was contextualised for their stakeholders. Analysis was provided by Accelerate CIC Lymphoedema & Leg Ulcer Clinic. Results: A total of 2885 patients were reviewed via an online or a paper audit tool. In total, 2721 patients had one or more active wounds. However, 1350 patients had one or more lower leg wounds, with 164 patients being managed for lower limb swelling or prevention of leg ulceration; bilateral conditions ranged from 11–43% across audit sites. Of the six sites, two included both community and primary care providers, thus generating wound point prevalence data. The remaining four sites audited community nursing and podiatry services only, with two sites collecting data on lower limb wounds only rather than all wounds, generating point prevalence for their services only. Compression usage varied across care locations, with the greatest use being seen in community leg ulcer clinics, where it was >96% for 234 residents. Compression usage was lower in the home with a range of 14–62% among 692 residents. For 263 residents, where the cause of their lower leg wound was unknown, compression usage was very low at 12%. Compression usage decreased with age; for three audit sites this was noteworthy, with 65% of those aged >80 years not in receipt of compression. Compression usage had a direct impact on nursing activity; non-use of compression increased activity by 37%. Conclusion: Through the identification of wound location, this series of wound prevalence audits identified a greater number of patients with lower limb wounds than those recognised and classified as a leg ulcer. Substantial variation in access to diagnostics and compression therapy was observed between audit sites, and also between locations within their boroughs. The factors that reduced access to compression therapy included not classifying the lower leg wound as a leg ulcer, being cared for in the home and increasing age of the patient. Lack of compression usage increased nursing activity. Where there is lack of access to therapeutic intervention, the resultant patient harm is not systematically recognised or documented.